Motif Penggunaan Aplikasi TikTok pada Siswa SMA N 2 Boyolali Ditinjau dari Teori Motif Alfred Schutz - Azizah, Naning Nur; Liestyasari, Siany Indria; Zuhri, Saifuddin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The development of globalization has brought information technology to develop rapidly in aspects of life, especially the emergence of new media, namely TikTok. Many things underlie a person's behavior in using social media so that it provides a variety of patterns. This study aims to explain the motives for the TikTok application among SMA N 2 Boyolali students and what patterns are formed. This research uses a qualitative method with a phenomenological approach. Data collection techniques in this study used observation, interviews, and document review. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results showed that there are patterns of using the TikTok application in the form of diversion patterns used for entertainment, patterns of increased intensity use at night, to patterns created for informative purposes. The use of TikTok has many motives, it can even give rise to derivative motives due to its use. Broadly speaking, there are two main motives, namely the "because" motive which explains the reasons for using TikTok by students. This motive is an effort to adjust to trends, space for self-expression, and opportunities for economic activity. Meanwhile, the "for" motive is more future-oriented, such as investing in social capital, wanting to become content creators and influencers.